2013
DOI: 10.1186/1824-7288-39-81
|View full text |Cite
|
Sign up to set email alerts
|

Application of a score system to evaluate the risk of malnutrition in a multiple hospital setting

Abstract: BackgroundAn increased but unpredictable risk of malnutrition is associated with hospitalization, especially in children with chronic diseases. We investigated the applicability of Screening Tool for Risk of Impaired Nutritional Status and Growth (STRONGkids), an instrument proposed to estimate the risk of malnutrition in hospitalized children. We also evaluated the role of age and co-morbidities as risk for malnutrition.MethodsThe STRONGkids consists of 4 items providing a score that classifies a patient in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1
12

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 34 publications
7
47
1
12
Order By: Relevance
“…We also found a significant relationship between having a "high risk" score and younger age of the children. These results are in accordance not only with findings of the original publication of the STRONGkids in Dutch population but also with another recent study that tested the use of the STRONGkids in Italian hospitalized children [6,12]. This altogether confirms the validity of the STRONGkids questionnaire in different countries, as well as in Croatia.…”
Section: Discussionsupporting
confidence: 91%
“…We also found a significant relationship between having a "high risk" score and younger age of the children. These results are in accordance not only with findings of the original publication of the STRONGkids in Dutch population but also with another recent study that tested the use of the STRONGkids in Italian hospitalized children [6,12]. This altogether confirms the validity of the STRONGkids questionnaire in different countries, as well as in Croatia.…”
Section: Discussionsupporting
confidence: 91%
“…Hand searching of the reference lists and expert contacts yielded 1 extra article each (26,27). The flow diagram of the study selection process is shown in Figure 1.…”
Section: Search Resultsmentioning
confidence: 99%
“…Children with a score ≥2 were eligible for study participation. STRONGkids is a nutritional screening tool for hospitalized children based on a questionnaire that does not include any anthropometric measures [14,15,16,17]. The method has not been validated for critically ill children.…”
Section: Important Points and Questionsmentioning
confidence: 99%